The Evaluation of Amil's Rights to Zakat, Infaq, and Charity Through the Perspective of Organizational Culture and BAZNAS Ratio - Esakariani, Nur Sakinah; Santoso, Rahmat Agus (Universitas Brawijaya, Indonesia, 2025)
This study addresses the urgent need to improve compliance and governance in zakat institutions, specifically in managing amil rights, which play a key role in operational sustainability. This study aims to evaluate the management of amil rights through the lens of organizational culture and the amil rights ratio as regulated by BAZNAS, applied to the case of LAZISMU Gresik. This qualitative explanatory study employs a single case study method. Data were collected through in-depth interviews with three key informants: the Management Board Secretary, the Branch Manager, and the Financial Manager of LAZISMU Gresik, selected using purposive sampling based on their roles in financial and cultural decision-making. Additional data were gathered through document analysis, including audited financial statements from 2019 to 2023, as well as non-participant observation. The findings reveal that while the amil rights ratio to zakat and infaq individually complies with BAZNAS standards, the overall ZIS ratio often exceeds the recommended threshold due to the dominance of infaq over zakat in the revenue structure. An organizational culture characterized by transparency, professionalism, and integrity is found to be a key factor in maintaining financial discipline despite challenges in the ratio. This study introduces a novel integration of financial ratio analysis with organizational culture interpretation, offering insights for zakat institutions and regulators on enhancing internal governance frameworks.